Chest CT findings in asymptomatic cases with COVID-19: a systematic review and meta-analysis. Issue 11 (November 2020) - Tsikala Vafea, M.; Atalla, E.; Kalligeros, M.; Mylona, E.K.; Shehadeh, F.; Mylonakis, E.
Abstract : AIM: To determine the overall rate of chest imaging findings in asymptomatic cases, describe the most common patterns found, and determine the rate of later symptom development in these initially asymptomatic cases. MATERIALS AND METHODS: The PubMed and EMBASE databases were searched until 1 May 2020, for studies examining the proportion of positive chest imaging findings in asymptomatic cases diagnosed with COVID-19 and a random-effects meta-analysis of proportions was performed. Heterogeneity was assessed using the I 2 statistic. RESULTS: Among 858 non-duplicate studies, seven studies with a total of 231 asymptomatic cases met the inclusion criteria. In the primary analysis, the pooled estimate of the overall rate of positive chest computed tomography (CT) findings among asymptomatic cases was 63% (95% confidence interval [CI]: 44–78%). Among 155/231 cases that were followed up for later symptom development, 90/155 remained asymptomatic and 65/155 developed symptoms during the study period (that ranged between seven and 30 days of follow-up). The pooled estimate of the rate of positive chest CT findings was 62% (95% CI: 38–81%) in cases that remained asymptomatic, while it was 90% (95% CI: 49–99%) in cases that developed symptoms. Among CT findings, the pooled estimate of the overall rate of ground-glass opacities (GGO) at CT alone was 71% (95% CI: 50–86%). Among other CT findings reported, 22/231 patients had GGO with consolidation, 7/231 patients had stripe shadows with or without GGO, and 8/231 patients had GGO with interlobular septal thickening. Among initially asymptomatic cases with positive CT findings, the pooled estimate of the overall rate of later symptom development was 26% (95% CI: 14–43%). CONCLUSION: In COVID-19, asymptomatic cases can have positive chest CT findings, and COVID-19 should be considered among cases with CT abnormalities even when there are no other symptoms. There is a need for close clinical monitoring of asymptomatic cases with radiographic findings as a significant percentage will develop symptoms. Highlights: In COVID-19, asymptomatic cases can have positive chest CT findings. COVID-19 should be considered among cases with CT findings even without symptoms. Clinical monitoring of asymptomatic cases with radiographic findings is needed. A significant percent of asymptomatic cases with CT findings will develop symptoms.